Characterization Study forNanocompositions of Methylene Blueand Riboflavin-Nafion on the Electrode Surface: Characterization of nanocompositions on electrode surface - Saeed Rezaei-Zarchi,; Ali Akbar Saboury,; Aisha Javed, (Iranian Journal of Pharmaceutical Sciences, 2008)
Nafion is a perfluorinated anionic polyelectrolyte. The increasing popularity of nafion for the fabrication of redox polymer modified electrodes in recent years arises from easy fabrication, good electrical conductivity and high partition coefficients of many redox compounds in nafion. To investigate the production of nano-compositions by mixing electron transfer material and nafion polymer for the modification of electrodes, a functional membrane composed of nano-particles of methylene blue, and nafion was constructed. The materials were characterized by the methods of scanning electron microscopy (SEM), transmission electron microscopy (TEM), ultraviolet (UV)-visible and FT-IR. The average diameter of new nano-particles was estimated to be about 60 nm. Anovel nafion-riboflavin membrane was also constructed and characterized by the methods of SEM, TEM and UV-visible spectroscopy. The estimated average diameter of new nanoparticles was about 60 nm. Our data has proven that nafion can be very interesting and helpful material in constructing nanoparticles of different electro-active materials and it can immobilize this material with a very good stability.